The Effect of Agile Leadership, Organizational Culture and Dynamic Capabilities on Organization Agility Mediated by Innovation in Automotive Manufacturing Companies - Dwi Astuti; S.Pantja Djati; Wahyuningsih Santosa (International Journal of Economics Development Research (IJEDR), 2023)
The purpose of this study was to analyze the influence of agile Leadership, Organizational Culture and Dynamic Capability on Organization Agility with Innovation as a mediating variable in automotive manufacturing companies in the Bekasi industrial area. The research method used in this study is quantitative research. Based on the Haier Sampling calculation, which is 5 times 73 indicators, it is known that the number of samples is 365 respondents who are middle and top management leaders with questionnaires distributed to respondents, namely 370 questionnaires. Data analysis in this study used the SEM-PLS (Structural Equation Model-Partial Least Squares) method with SmartPLS 3.0 software.  The results of this study indicate that agile Leadership has a positive influence on Organization Agility. Organizational Culture has also been shown to have a positive effect on organizational agility. However, no significant effect was found from dynamic capabilities on organizational agility. Innovation plays a positive role in increasing Organizational Agility. Agile Leadership has a direct effect on innovation. Dynamic Capabilities have a positive impact on innovation, as well as organizational culture has an effect on innovation. In addition, agile leadership and organizational culture also affect organizational agility through innovation. Dynamic Capabilities also have a positive effect on organizational agility through innovation. The implication of this study is that Agile leadership and a supportive organizational culture play an important role in enhancing agility and innovation in the manufacturing sector. Management should encourage agile leadership by accelerating decision-making processes, improving transcription, and encouraging collaboration, as well as building an adaptive and collaborative culture. Although dynamic capabilities do not directly increase agility, they are still important to support innovation and adaptability. Continuous innovation in products, processes, and technologies must be driven through a culture that encourages creativity and learning from failure. By investing in the development of dynamic capabilities and new technologies, companies can continue to maintain competitiveness and responsibility in a dynamic market.